The Motivation Bridge: How Career Development and Work Environment Shape Job Satisfaction via Work Motivation - M. Haikal Wahyudi; Laila Refiana Said; Meiske Claudia; Hastin Umi Anisah; Ahmad Rifani (International Journal of Economics, Business and Innovation Research, 2026)
Teacher job satisfaction plays an important role in maintaining the quality of learning in schools. This study aims to analyze the effect of career development and work environment on teacher job satisfaction, with work motivation as a mediating variable. The study was conducted on 53 subject teachers at a public high school in Banjarmasin using a quantitative approach through questionnaires and analyzed using SEM-PLS. The results show that career development and work environment have a positive and significant effect on work motivation and job satisfaction. Work motivation also has a positive and significant effect on job satisfaction, and mediates the relationship between career development and job satisfaction, as well as between work environment and job satisfaction. These findings confirm that efforts to strengthen career development programs and create a conducive work environment not only increase job satisfaction directly but also through increased teacher work motivation.